CATALISE: A multinational and multidisciplinary Delphi consensus study. Identifying language impairments in children - Dorothy V.M. Bishop; Margaret J. Snowling; Paul A. Thompson; Trisha Greenhalgh; Catherine Adams; Lisa Archibald; Gillian Baird; Ann Bauer; Jude Bellair; Christopher Boyle; Elizabeth Brownlie; Glenn Carter; et al. (PLOS One, 2025)
Delayed or impaired language development is a common developmental concern, yet there
is little agreement about the criteria used to identify and classify language impairments in
children. Children's language difficulties are at the interface between education, medicine
and the allied professions, who may all adopt different approaches to conceptualising them.
Our goal in this study was to use an online Delphi technique to see whether it was possible
to achieve consensus among professionals on appropriate criteria for identifying children
who might benefit from specialist services. We recruited a panel of 59 experts representing
ten disciplines (including education, psychology, speech-language therapy/pathology, paediatrics
and child psychiatry) from English-speaking countries (Australia, Canada, Ireland,
New Zealand, United Kingdom and USA). The starting point for round 1 was a set of 46
statements based on articles and commentaries in a special issue of a journal focusing on
this topic. Panel members rated each statement for both relevance and validity on a sevenpoint
scale, and added free text comments. These responses were synthesised by the first
two authors, who then removed, combined or modified items with a view to improving consensus.
The resulting set of statements was returned to the panel for a second evaluation
(round 2). Consensus (percentage reporting 'agree' or 'strongly agree') was at least 80 percent
for 24 of 27 round 2 statements, though many respondents qualified their response
with written comments. These were again synthesised by the first two authors. The resulting
consensus statement is reported here, with additional summary of relevant evidence, and a
concluding commentary on residual disagreements and gaps in the evidence base.